Animals in the Public Debate: Welfare, Rights, and Conservationism in India - Berti, Daniela (Religions, 2019)
This paper proposes a survey of the many ways in which people look at and deal with animals in contemporary India. On the basis of ethnographic research and of multiple written sources (judgments, newspapers, websites, legal files, activist pamphlets, etc.), I present some of the actors involved in the animal debate—animal activists, environmental lawyers, judges, and hunter-conservationists—who adopt different, though sometimes interconnected, approaches to animals. Some of them look at animals as victims that need to be rescued and treated in the field, others fight for animals in Parliament or in Court so that they can be entitled to certain rights, others are concerned with the issue of species survival, where the interest of the group prevails on the protection of individual animals. In the context of a predominantly secularist background of the people engaged in such debates, I also examine the role that religion may, in certain cases, play for some of them: whether as a way of constructing a Hindu or Buddhist cultural or political identity, or as a strategic argument in a legal battle in order to obtain public attention. Lastly, I raise the question of the role played by animals themselves in these different situations—as intellectual principles to be fought for (or to be voiced) in their absence, or as real individuals to interact with and whose encounter may produce different kinds of sometimes conflicting emotions.